Improving Financial Administration in Urban Perfume Point MSMEs - Erika Martha Ayu Ningtyas; Nuvriasari, Audita (PT FORMOSA CENDEKIA GLOBAL, 2023)
MSMEs in running their business need to pay attention to a number of management aspects, one of which is financial management. The aim of this activity is to improve financial administration at Urban Perfume Point and increase the knowledge of Urban Perfume Point employees in recording business finances both conventionally and based on information technology. The method used is the transfer of knowledge ad technology through outreach and training activities as well as work internships. The results of the activity show that the administration of financial management at Urban Perfume Point has experienced an improvement as shown by the orderliness of business financial records.